Comparison of selected kinematic structure parameters in male and female high jumpers - Slamka, M.; Moravec, R. (Kinesiologia Slovenica, 1999)
This work deals with selected parameters of high jump technique of top-performance competitors. Eighteen tries of men and twenty-one tries of women were evaluated by means of two-dimensional analysis. Results of males were between 205 and 229 cm, females between 175 and 205 cm. The discussed parameters are sports performance, culmination of trajectory of the centre of gravity and vertical velocity at the end of take-off.